An innovative investigation on the workpiece kinematics and its roundness generation in through-feed centreless grinding. (May 2017) - Cui, Qi; Cheng, Kai; Chen, Shijin; Ding, Hui
In order to continuously improve the component roundness and productivity, an innovative investigation on through-feed centreless grinding is required particularly towards the 0.1–0.3 µm roundness accuracy of the components in the industrial production scale. In this process, the characteristics of the supporting and driving mechanism for the workpiece make the analysis of workpiece surface generation more complex than other grinding processes. This article presents an innovative approach for investigating the workpiece roundness generation in through-feed centreless grinding. Using homogeneous transformations, the geometries and the movements of the workpiece and the wheels are presented through a three-dimensional simulation model developed by the authors. This model and the associated simulations can be applied to investigate the workpiece kinematics and its rounding process under various geometric configurations and grinding parameters, and to further analyse the influences of these parameters on the workpiece roundness generation.